Web-Based Slaughterhouse Monitoring Information System Using ERD Method - Harahap, Eka Purnama; Permana, Ridwan Yoga; Firmansyah, Ricko; Fathoni, Muhammad Irzal (UNIVERSITAS RAHARJA, 2025)
The advancement of information technology drives the livestock sector, especially slaughterhouses (RPH), to adopt digital solutions. This study develops a web-based RPH monitoring information system to support real-time recording, animal health monitoring, scheduling, and reporting. Data collection was conducted through interviews and literature studies, while the database design applied the Entity Relationship Diagram (ERD) method to ensure organized and scalable data structures. The system was developed using PHP and MySQL and is accessible to both operational staff and relevant institutions. The results show that the system improves efficiency, recording accuracy, and operational transparency of slaughterhouses. Additionally, it enhances public trust and facilitates data-driven decision-making.